Utilization of Plastic Waste With Ecobricks: Education and Training for Junior High School Students - Adriyani, Retno; Sulistyowati, Muji; Pratiwi, Damai Arum; Farapti, Farapti; Prameswari, Atika Anif; Hadyandiono, Chrisna Nur; Safaryna, Alifia M; Azmy, Ulul (Journal of Innovation and Applied Technology, 2025)
This community service program aimed to enhance environmental awareness and practical skills in plastic waste management among junior high school students in Banraas and Bancamara villages on Gili Iyang Island, Madura. Ecobricks are defined as plastic bottles densely packed with cleaned plastic waste to form durable, reusable building blocks. The training combined lecture-based sessions using fan media to explain the hazards of plastic pollution and introduce the concept and benefits of ecobricks followed by ecobricks practice for students. Pre-posttest revealed that the proportion of students score in the low category decreased from 10 percent to 0 percent, while those achieving high scores increased by 77 percent. Practical engagement was further demonstrated by enthusiastic participation in ecobrick assembly and quiz activities, and production of a simple table from ecobricks. This integrated approach successfully fostered students’ environmental responsibility, creative reuse practices, and community-wide promotion of sustainable waste management.